2020
DOI: 10.1038/s41467-019-13928-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided design of pure orthosteric inhibitors of αIIbβ3 that prevent thrombosis but preserve hemostasis

Abstract: A prevailing dogma is that inhibition of vascular thrombosis by antagonizing platelet integrin αIIbβ3 cannot be achieved without compromising hemostasis, thus causing serious bleeding and increased morbidity and mortality. It is speculated that these adverse outcomes result from drug-induced activating conformational changes in αIIbβ3 but direct proof is lacking. Here, we report the structure-guided design of peptide Hr10 and a modified form of the partial agonist drug tirofiban that act as "pure" antagonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 70 publications
(66 reference statements)
0
35
0
1
Order By: Relevance
“…Ligands in the blood such as fibrinogen (and other proteins) bind to integrin αIIbβ3 receptors, and bridge activated platelets. 46 This leads to platelet aggregation and the formation of a platelet plug that prevents bleeding from a damaged vessel. 711 Secondary hemostasis occurs concurrently with primary hemostasis and involves the activation of factors in intrinsic and extrinsic pathways of the coagulation cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Ligands in the blood such as fibrinogen (and other proteins) bind to integrin αIIbβ3 receptors, and bridge activated platelets. 46 This leads to platelet aggregation and the formation of a platelet plug that prevents bleeding from a damaged vessel. 711 Secondary hemostasis occurs concurrently with primary hemostasis and involves the activation of factors in intrinsic and extrinsic pathways of the coagulation cascade.…”
Section: Introductionmentioning
confidence: 99%
“…The histogram in Fig. 1 shows the expression level of integrins on the surface of human melanoma cells, M21 using specific antibodies [7].…”
Section: Integrin Cell Surface Levelmentioning
confidence: 99%
“…We used the following model cells derived from the same cell line: M21, expressing avb3 and a5b1; M21L, expressing only a5b1; and M21GPIIb, expressing aIIbb3 and a5b1, but not avb3 [7]. Cells were grown on surfaces without specific coating and/or with fibronectin, and the elasticity was probed using atomic force microscopy to answer the following questions: The results from these measurements were compared with previous stiffness measurements of the same cell lines using a microfluidic device under non-adherent cellular conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RGD‐like compounds may behave as true agonists mimicking the ECM natural ligand‐dependent activation of integrins and subsequent pro‐tumoral signaling pathways [41] . Very interestingly, recent developments on integrin pure antagonists have been published supporting a new area in integrin ligand research [81–84] . Based on electron microscopy, X‐ray crystallography and receptor priming studies, it was shown that these new classes of integrin antagonists do not induce the integrin conformational changes associated with activation.…”
Section: Rgd‐integrin Ligandsmentioning
confidence: 99%